2000
DOI: 10.1034/j.1399-3003.2000.016003397.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of vitamin C with the relation between smoking and obstructive airways disease in EPIC Norfolk

Abstract: Previous studies have reported an association between plasma vitamin C levels and respiratory function, but have not examined the role of vitamin C as an effect modifier of the relation between cigarette smoking and obstructive airways disease (OAD).This question was investigated in a cross-sectional analysis of a population-based study of 3,714 males and 4,256 females aged 45±74 yrs. Undiagnosed OAD was defined as a forced expiratory volume in one second (FEV1) of <80% of the predicted value and FEV1/forced v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Presumably, a reduction of VC in the lungs resulted in an enlargement of the air space without alveolar destruction, but complete lack of VC in the lungs generated pulmonary emphysema. Several epidemiologic studies indicate that dietary factors, particularly VC, may be involved in the etiology of COPD (31,41,44). A prospective study of dietary intake of antioxidant vitamins (vitamins A, C, and E) and decline of lung function performed in a general population consisting of 2,663 adults aged 18 -70 living in the United Kingdom identified a significant correlation between declining lung function and intake of VC but not vitamins A or E (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, a reduction of VC in the lungs resulted in an enlargement of the air space without alveolar destruction, but complete lack of VC in the lungs generated pulmonary emphysema. Several epidemiologic studies indicate that dietary factors, particularly VC, may be involved in the etiology of COPD (31,41,44). A prospective study of dietary intake of antioxidant vitamins (vitamins A, C, and E) and decline of lung function performed in a general population consisting of 2,663 adults aged 18 -70 living in the United Kingdom identified a significant correlation between declining lung function and intake of VC but not vitamins A or E (31).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate that VC has a beneficial effect on lung function but, when depleted during aging, may promote chronic obstructive pulmonary disease (COPD; Refs. 41,44). On the other hand, VC also plays an essential role in collagen synthesis because it acts as a cofactor for prolyl hydroxylase to catalyze hydroxyproline synthesis, which is involved in collagen helix stabilization (33,38).…”
mentioning
confidence: 99%
“…Hu et al [20] found that in rural China, vitamin C intake was significantly positively associated with FEV 1 . Sargeant et al [18] found that plasma vitamin C, used as a marker for dietary vitamin C, had a protective effect against the risk of undiagnosed obstructive airways disease defined on the basis of FEV 1 .…”
Section: Vitamins C and Ementioning
confidence: 99%
“…Vitamin A deficiency promotes bronchial hypersensitivity in rats [3] and is reduced in asthmatic children [4]. Sargeant et al reported that a 20 mmol/L increase in plasma vitamin C is associated with a 13% reduction in the risk of developing obstructive airway disease [5]. Reduced vitamin D levels are associated with impaired lung function and increased airway hyperresponsiveness in adult asthma [6,7].…”
Section: Introductionmentioning
confidence: 99%